Trauma of the Frontal Region Is Influenced by the Volume of Frontal Sinuses. A Finite Element Study - Pajic, Srbislav S.; Antic, Svetlana; Vukicevic, Arso M.; Djordjevic, Nenad; Jovicic, Gordana; Savic, Zivorad; Saveljic, Igor; Janović, Aleksa; Pesic, Zoran; Djuric, Marija; Filipovic, Nenad (Frontiers in Physiology, 2017)
Anatomy of frontal sinuses varies individually, from differences in volume and shape to a rare case when the sinuses are absent. However, there are scarce data related to influence of these variations on impact generated fracture pattern. Therefore, the aim of this study was to analyse the influence of frontal sinus volume on the stress distribution and fracture pattern in the frontal region. The study included four representative Finite Element models of the skull. Reference model was built on the basis of computed tomography scans of a human head with normally developed frontal sinuses. By modifying the reference model, three additional models were generated: a model without sinuses, with hypoplasic, and with hyperplasic sinuses. A 7.7 kN force was applied perpendicularly to the forehead of each model, in order to simulate a frontal impact. The results demonstrated that the distribution of impact stress in frontal region depends on the frontal sinus volume. The anterior sinus wall showed the highest fragility in case with hyperplasic sinuses, whereas posterior wall/inner plate showed more fragility in cases with hypoplasic and undeveloped sinuses. Well developed frontal sinuses might, through absorption of the impact energy by anterior wall, protect the posterior wall and intracranial contents.